Subclinical cardiovascular disease in patients starting contemporary protease inhibitors. Issue 7 (10th May 2018) - González‐Cordón, A; Doménech, M; Camafort, M; Martínez‐Rebollar, M; Torres, B; Laguno, M; Rojas, J; Loncà, M; Blanco, JL; Mallolas, J; Gatell, JM; de Lazzari, E; et al.
Abstract : Objectives: The aim of the study was to assess changes in and factors associated with anatomical [carotid artery intima‐media thickness (CIMT)] and functional (arterial stiffness) markers of subclinical cardiovascular disease progression in antiretroviral‐naïve patients starting triple combination antiretroviral therapy containing contemporary protease inhibitors. Methods: This was a planned substudy of the ATADAR (Metabolic Effects of Atazanavir/Ritonavir Versus Darunavir/Ritonavir in Combination With Tenofovir/Emtricitabine in naïve HIV‐1 Infected Patients) clinical trial (ClinicalTrials.gov identifier NCT01274780). ATADAR is a multicentre, randomized, open‐label clinical trial comparing the effects of ritonavir‐boosted atazanavir and darunavir, both with tenofovir/emtricitabine, in antiretroviral‐naïve HIV‐infected patients. Common CIMT and aortic augmentation index (AIx@75) were measured at baseline and after 12 months of follow‐up. Antiretroviral treatment, traditional cardiovascular risk factors and HIV‐related factors were assessed as potential predictors of CIMT and Aix@75 changes using linear regression analysis. Results: Thirty‐three patients were included in this pilot study. While CIMT significantly increased in the pooled population [median (interquartile range (IQR)) 68 (−13, 128) μm; P = 0.0511], AIx@75 did not [median (IQR) 1 (−6, 5)%; P = 0.8964]. Patients on darunavir showed a trend to faster CIMT progression than those on atazanavir [median change (IQR) 117 (−2, 143) vs . −6 (−58, 89) μm, respectively; P = 0.0917]. However, after adjustment in the multivariate analysis, a higher baseline Framingham score was the only factor associated with CIMT progression (coefficient 16.02; 95% confidence interval –1.04, 33.08; P = 0.064). AIx@75 change was not associated with any baseline factor. Conclusions: CIMT was a more sensitive marker of subclinical vascular disease progression than arterial stiffness in antiretroviral‐naïve patients starting antiretroviral therapy with contemporary protease inhibitors. Classical risk factors but not antiretroviral therapy were associated with faster CIMT progression.